Muzykolodzy pochodzenia żydowskiego we Lwowie (przed 1939 r.) - Melnyk, Lidia (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
Lviv’s diverse cultural landscape, shaped by Polish, Jewish, and Ukrainian communities, significantly influenced its musical and academic life. Focusing on three notable Jewish figures – J. Freiheiter, I.Spiegel-Hüssowa and Z.Lissa – the study highlights their contributions and challenges as disciples of Adolf Chybinski. Their educational paths, professional achievements, and tragic fates during WWII are examined. This research fills a gap in the historical narrative of Lviv’s musicology, highlighting the substantial role played by Jewish scholars.